Resistant Starch from Purple Sweet Potatoes Alleviates Dextran Sulfate Sodium-Induced Colitis through Modulating the Homeostasis of the Gut Microbiota - Zhihao Wang; Min Gao; Juan Kan; Qingyang Cheng; Xiaotong Chen; Chao Tang; Dan Chen; Shuai Zong; Changhai Jin (Foods, 2024)
Ulcerative colitis (UC) is a complicated inflammatory disease with a continually growing incidence. In this study, resistant starch was obtained from purple sweet potato (PSPRS) by the enzymatic isolation method. Then, the structural properties of PSPRS and its protective function in dextran sulfate sodium (DSS)-induced colitis were investigated. The structural characterization results revealed that the crystallinity of PSPRS changed from CA-type to A-type, and the lamellar structure was totally destroyed during enzymatic hydrolysis. Compared to DSS-induced colitis mice, PSPRS administration significantly improved the pathological phenotype and colon inflammation in a dose-dependent manner. ELISA results indicated that DSS-induced colitis mice administered with PSPRS showed higher IL-10 and IgA levels but lower TNF-α, IL-1β, and IL-6 levels. Meanwhile, high doses (300 mg/kg) of PSPRS significantly increased the production of acetate, propionate, and butyrate. 16S rDNA high-throughput sequencing results showed that the ratio of Firmicutes to Bacteroidetes and the potential probiotic bacteria levels were notably increased in the PSPRS treatment group, such as Lactobacillus, Alloprevotella, Lachnospiraceae_NK4A136_group, and Bifidobacterium. Simultaneously, harmful bacteria like Bacteroides, Staphylococcus, and Akkermansia were significantly inhibited by the administration of a high dose of PSPRS (p < 0.05). Therefore, PSPRS has the potential to be a functional food for promoting intestinal health and alleviating UC.